Application for Lecturer Recruitment Using Simple Additive Weighting (SAW) Method Case Study: Tanri Abeng University Jakarta - Pramitha Dwi Larasati; Ari Irawan (Depart. of Information Systems, FST, UIN Syarif Hidayatullah Jakarta, 2020)
In the selection of acceptance of lecturers at a university can be done when the selected applicants have a good competence in accordance with they’re background because this can affect the teaching service. Lecturers who have good competence has the ability for understanding the subject matter that in line with the background, extensive pieces of knowledge, be able to speak English both oral and written and be able to provide a positive example and teaching methods that are easily understood by students. This can provide a good image for the university because the selected lecturers have a good potential. To help determine the acceptance of lecturers then we needed a decision support system. One method that can be used for Decision Support System is using Simple Additive Weighting (SAW). This method is chosen because it is able to select the best alternative from a number of alternatives, in this case, the intended alternative is to determine the acceptance of lecturers